Environmental economics and investment assessment II - Brebbia, C A (WIT, 2015)
The emphasis on sustainable development has resulted in the need to assess the impact of economic investments on the environment. The main question being, is the development of enterprise compatible with environmental protection? This book addresses this problem by discussing and proposing progressive approaches for achieving sustainability.